2014
DOI: 10.1371/journal.pone.0095512
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the Protein Lysine and Arginine Methylation Network in Arabidopsis Chloroplasts

Abstract: Post-translational modification of proteins by the addition of methyl groups to the side chains of Lys and Arg residues is proposed to play important roles in many cellular processes. In plants, identification of non-histone methylproteins at a cellular or subcellular scale is still missing. To gain insights into the extent of this modification in chloroplasts we used a bioinformatics approach to identify protein methyltransferases targeted to plastids and set up a workflow to specifically identify Lys and Arg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 72 publications
1
53
0
Order By: Relevance
“…The lack of NME for just RBCS is likely due to the presence of a bulky residue (Lys) immediately after the Met. It should be noted that Lys methylation has been observed for several Arabidopsis chloroplast proteins downstream of their mature Nti Alban et al, 2014). Lys-14 of RBCL has been shown in pea (Pisum sativum) to be (tri)methylated (Houtz et al, 2008).…”
Section: Physiological Nt Methylationmentioning
confidence: 99%
“…The lack of NME for just RBCS is likely due to the presence of a bulky residue (Lys) immediately after the Met. It should be noted that Lys methylation has been observed for several Arabidopsis chloroplast proteins downstream of their mature Nti Alban et al, 2014). Lys-14 of RBCL has been shown in pea (Pisum sativum) to be (tri)methylated (Houtz et al, 2008).…”
Section: Physiological Nt Methylationmentioning
confidence: 99%
“…Acetylation and methylation of chloroplast proteins have been identified recently (Houtz et al, 1992;Finkemeier et al, 2011;Wu et al, 2011;Mininno et al, 2012;Alban et al, 2014). Therefore, the acetylation and methylation states of the four membrane-bound AtFNR forms were analyzed.…”
Section: Atfnr1 and Atfnr2 Are Lys Acetylatedmentioning
confidence: 99%
“…A recent study has identified 23 chloroplast methylproteins (Alban et al, 2014), including the previously described ALDOLASE isoforms (Mininno et al, 2012) and PLASTID RIBOSOMAL PROTEIN L11 (Yamaguchi and Subramanian, 2000). Four out of these 23 proteins contained one or more methylated Arg residues, while 17 proteins had Lys methylation.…”
Section: Lys and Arg Methylationmentioning
confidence: 96%
“…RBCL and ATP SYNTHASE b-subunit were methylated at both Lys and Arg residues (Alban et al, 2014). In addition to Rubisco and FRU-1,6-BISPHOSPHATE ALDOLASE, five additional proteins functioning in CO 2 assimilation were methylated (Alban et al, 2014). Interestingly, chloroplast protein methylation is, at least partly, induced by light (Niemi et al, 1990).…”
Section: Lys and Arg Methylationmentioning
confidence: 99%
See 1 more Smart Citation